The Influence Of Product Quality, Price Perceptions, And Sales Promotions On Purchasing Decisions: Case study at the House of Donatello in Bogor - Zuhdi, Saefudin; Primandini, Delia; Sujana, Sujana (LPPM Institut Bisnis dan Informatika Kesatuan, 2024)
This study aims to: (1) To determine the effect of Product Quality on Purchasing Decisions, (2) To determine the effect of Perceived Price on Purchasing Decisions, (3) To determine the effect of Sales Promotion on Purchasing Decisions, (4) To determine the effect of Product Quality, Price Perceptions, and Sales Promotion on Purchasing Decisions. The number of samples is 386 respondents using the Slovin formula. The data analysis method used is multiple linear regression analysis to determine the effect of Product Quality, Perceived Price and Sales Promotion on Purchasing Decisions in case studies of House of Donatello at Bogor. Data testing is done by using Statistical Package for the Social Scientist (SPSS) Software.Based on the test, the following data are obtained: (1) There is an effect of Product Quality on Purchasing Decisions (2) There is an effect of Perceived Price on Purchase Decisions (3) There is an influence of Sales Promotion on Purchase Decisions (4) There is an influence between Product Quality, Perceived Price, and Sales Promotion on Purchasing Decisions. Keywords: Product Quality, Price Perception, Sales Promotion, Purchase Decision